REFORMING THE PENSION SYSTEM: INTERNATIONAL EXPERIENCE AND OUTCOMES - Khayitmurodova, Durdona; Jumaboyeva, Kumush (Journal of Fundamental Studies, 2026)
The purpose of this article is to analyze the significance of pension system reform based on international experience and to identify appropriate directions for Uzbekistan. The research methodology is grounded in a systematic literature review and comparative analysis. The findings indicate that pension system reforms are directly conditioned by countries’ levels of economic development, demographic dynamics, and institutional capacity. The experiences of Sweden and the Netherlands demonstrate the effectiveness of stable and balanced models, while the cases of Chile and Mexico highlight the critical importance of regulatory oversight and social protection mechanisms. In Uzbekistan, a high level of informal employment and limited financial inclusion adversely affect the overall efficiency of the system. In conclusion, a gradual reform approach that integrates state guarantees, private sector participation, robust regulatory frameworks, and enhanced financial literacy is recommended as the most appropriate pathway for pension system development.